Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja terhadap Kinerja Pegawai - Ezra Christina Marpaung; Muhammad Ikhsan; Nurmala Pangaribuan (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
ABSTRACT The purpose of this research is to determine the influence of leadership style and job satisfaction on employee performance at RSUD Dr. Hadrianus Sinaga Pangururan. The method used in this research is a quantitative approach from an associative research strategy. Data collection techniques use questionnaires. The data analysis technique uses Simple Linear Regression. The results of the research show that the leadership style consisting of transformational leadership, transactional leadership, and Laisses Faire leadership has a very positive and significant effect of 85.3% on employee performance, the rest is influenced by other variables. Job satisfaction consisting of salary, working conditions, company policies, interpersonal relationships, supervision, achievement, recognition, own work, and responsibility has a negative and significant effect of 40% on employee performance at RSUD Dr. Hadrianus Sinaga Pangururan in Samosir Regency. This means that the better the performance satisfaction, the weaker the employee's performance. In conclusion, leadership style and job satisfaction both influence employee performance in the form of improving employee performance (working according to targets, on time, and responding to patient complaints). Keywords: Employee Performance, Job Satisfaction, Leadership Style.